Ecohydrologie urbaine et changement climatique - P. Breil; A. Faty; D. Orange (Proceedings of the International Association of Hydrological Sciences, 2021)
Due to global change, cities of the future will have to deal with more intense runoff and longer drought sequences, in addition to a growing urban and peri-urban population. French Mediterranean cities, such as Toulon, are already densely urbanised and exposed to the effects of global warming. The adaptation of their infrastructures is problematic. Cities with high development potential, such as Dakar, offer the opportunity to imagine other solutions for the management of water resources and its extremes in the context of global change. In particular, it is a question of managing the flows of water and substances linked to intense runoff events according to an ecohydrological logic that makes it possible to reduce environmental risks and increase social and economic benefits. To do this, we use a hydrologically-based geomatics model (IRIP) that produces predictive maps of areas of generation, transfer and accumulation of intense runoff and associated nutrients. This allows us to target effective intervention areas to reduce risks and increase water resources, for example by simulating land use change in appropriate locations and at the same time stimulating specific biological processes. The fundamental principle of ecohydrology is to balance energy flows with biological metabolic flows at the sub-catchment scale. The mapping of intense runoff processes is a first step illustrated in this article for the cities of Toulon and Dakar. This first step is part of the Dakar'2030 project, which aims to rethink urban development and adapt it to climate change.